Organization of the integrated management system in the construction industry - Ichetovkin, A.A. (Ways to Improve Construction Efficiency, 2023)
The scientific article reveals the problems of finding innovative approaches to solving problems related to the organization of an integrated management system in the construction industry. Promising trends of integrated management in the construction sector, which are focused on the flexibility and adaptability of management systems to modern conditions, are studied. The ability to respond quickly to changes in market conditions and customer requirements is becoming key to the success of construction projects. The urgency of the problem of finding rational solutions for the organization of the integrated management system in the construction industry is indicated. The paper highlights the problems of organization of the integrated management system in the construction hall. Construction projects often come with risks, such as changes in the project, unforeseen circumstances, and technical complications. Integrated management systems must meet the challenges of risk management and provide flexibility in solving problems. Grounded prospects and opportunities for using an integrated management system that allows construction enterprises to be flexible and adaptable to changes in the internal and external environment. This is especially important in the face of rapid technological changes and volatile market conditions. As a result of the analysis, opportunities for the introduction of innovative technologies and methods in the construction industry have been identified. The integration of advanced solutions allows us to improve construction processes at all stages. The results of our research revealed the basic principles of applying an integrated management model under risk conditions for quality control modules in construction, based on the concept of dynamic systems. Therefore, we consider it expedient to introduce an integrated model risk and quality management in construction, and this requires further scientific research. The proposed method allows to harmonize the processes of quality management and risk management, taking into account the criteria of project efficiency, contributing to the avoidance of conflicts between the requirements for the quality of the construction object and the level of acceptable risks. In addition, this approach aligns them with the efficiency requirements for the developer. It is determined that the principles of using the integrated model of quality management in the face of risks include the principle of complementarity and the principle of identity of the management process. This made it possible to identify management modules that correspond to the concept of construction quality management in the face of risks as a dynamic system.